Core competencies of the midwifery workforce in China: A scoping review. (6th February 2022) - Li, Yuxuan; Lu, Hong; Zhao, Yang; Ren, Lihua; Cao, Linlin; Pang, Dong; Wang, Aihua
Abstract: Aim: This review aims to demonstrate the current core competencies of the Chinese midwifery workforce and to summarize the influencing factors of core competencies. Background: Midwifery core competencies are crucial to providing high‐quality maternal and newborn health care, but little is known about the overall status of the core competencies of the Chinese midwifery workforce. Evaluation: A scoping review was conducted following the latest Joanna Briggs Institute (JBI) scoping review methodology and Preferred Reporting Items for Systematic reviews and Meta‐Analyses extension for Scoping Reviews (PRISMA‐ScR) checklist. Key issues: Forty‐one studies were included in this review. Regarding core competency assessment tools, the Midwife Core Competency Scale was used most frequently among 16 identified tools. Generally, the core competencies of the Chinese midwifery workforce were at a moderate or high level, but the competencies in pre‐pregnancy, public health care and integrative competence were relatively inadequate. The main factors influencing the core competencies of the midwifery workforce were their working years, educational level and training experience. Conclusion: This review provides a comprehensive overview of the core competencies of the Chinese midwifery workforce at the national level. Future studies are encouraged to use objective instruments to reflect core competencies and explore the intervenable influencing factors of core competencies. Implications for Nursing Management: Core competency assessment tools can be used to select the qualified midwifery workforce. Targeted core competency enhancement programmes should be formulated based on the current core competencies level and the factors influencing core competencies.